Regenerative framework for a low-carbon energy Just Transition in coalfield communities, Western Ukraine - Hesketh, P; Ma, A; Griffiths, V; Kiviet, E (Mine Closure 2023: 16th International Conference on Mine Closure, 2023)
Despite the on-going conflict in the Ukraine, the Ukrainian government is still focused on developing plans to transition to a low carbon economy. The UK government has been supporting this with a pilot project to demonstrate how a Just Transition can be achieved through development of a Regeneration Framework for the town of Novovolynsk. This project has developed a post mining vision for two local mines that has been built from the bottom-up through a process of collaboratively engaging with key stakeholders to identify needs and develop a master vision for post mining land use. The master vision is set out in a regenerative framework which provides a clear road map for regeneration which enables social enhancement and promotes continued economic activity at the mine sites. To ensure that structural barriers are removed, the road map has been given clear alignment with Ukrainian regional and national policy, providing links to responsible closure, fairness in transition and equity and growth for the mining regions, thus strengthening the goals set out in the Regenerative Framework. This paper provides an update on the work undertaken over the last year and concluding the foundation element of the pilot project.
Keywords: coal; just transition; stakeholder engagement; master planning; mining; conflict regeneration